2014
DOI: 10.1186/1748-717x-9-162
|View full text |Cite
|
Sign up to set email alerts
|

High-dose proton beam therapy for sinonasal mucosal malignant melanoma

Abstract: BackgroundThe significance of definitive radiotherapy for sinonasal mucosal melanoma (SMM) is sill controvertial. This study was to evaluate the role of high-dose proton beam therapy (PBT) in patients with SMM.MethodsThe cases of 20 patients with SMM localized to the primary site who were treated by PBT between 2006 and 2012 were retrospectively analyzed. The patterns of overall survival and morbidity were assessed.ResultsThe median follow-up time was 35 months (range, 6–77 months). The 5-year overall and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
(25 reference statements)
1
30
0
Order By: Relevance
“…Overall toxicity in our cohort was moderate. Rates of high‐grade acute reactions, such as mucositis grade III with 28%, are comparable to previously published particle experience . However, it is noteworthy that these centres apply smaller target volumes than in our cohort due to the exclusion of cervical nodal levels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall toxicity in our cohort was moderate. Rates of high‐grade acute reactions, such as mucositis grade III with 28%, are comparable to previously published particle experience . However, it is noteworthy that these centres apply smaller target volumes than in our cohort due to the exclusion of cervical nodal levels.…”
Section: Discussionsupporting
confidence: 85%
“…Treatment between 52.8 and 64 GyE in 16 fractions resulted in 84% locoregional control at 5 years and 46.1% OS at 3 years in 72 patients treated with C12 . Proton RT in passive beam application with the addition of systemic chemotherapy showed very promising locoregional control of 70% at 3 years in 20 patients with gross residual disease (T4, 14 patients) . Zenda et al reported their locoregional control in 14 patients (T4, 64%) with 85.7% after treatment with 60 Gy protons in 15 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…25,4345 Proton therapy has been used to treat oropharyngeal cancers, sinonasal malignancies, and mucosal melanomas, although the clinical data are best established for ocular melanomas and chordomas. 4651 Single-institution outcome data have been reported for these H&N cancers, 43,4749,52,53 but the literature does not easily allow direct comparisons between proton therapy and IMRT; historical comparisons warrant cautious interpretation, because improvements in diagnosis and staging evaluations may lead to improvements in reported outcomes independent of therapy. Mindful of these caveats, a recent systematic review and meta-analysis of noncomparative observation studies concluded that patients with malignant diseases of the nasal cavity and paranasal sinuses who received proton therapy seemed to have better outcomes than those receiving photon therapy.…”
Section: Particle Therapiesmentioning
confidence: 99%
“…Compared with surgery in patients with sinonasal mucosal malignant melanoma, the continuous control of the primary lesions may achieve a higher survival rate (11).…”
Section: Pbt For Different Cancersmentioning
confidence: 99%